MAIT cells are activated during human viral infections - Van Wilgenburg, B; Klenerman, P; Willberg, C; Kurioka, A; Ramamurthy, N; Leng, T; De Lara, C; Scherwitzl, I; Hutchinson, E; Kulicke, C; Cole, S; Vasanawathana, S; et al. (Nature Publishing Group, 2016)
Mucosal Associated Invariant T (MAIT) cells are abundant in humans and recognise bacterial ligands. Here we demonstrate that MAIT cells are also activated during human viral infections in vivo. MAIT cells activation was observed during infection with Dengue virus, Hepatitis C virus, and Influenza Virus. This activation – driving cytokine release and Granzyme B upregulation - is TCR-independent but dependent on IL-18 in synergy with IL-12, IL-15 and/or interferon-α/β. IL-18 levels and MAIT cell activation correlate with disease severity in acute Dengue infection. Furthermore, HCV treatment with interferon-α leads to specific MAIT cell activation in vivo in parallel with an enhanced therapeutic response. Moreover, TCR- independent activation of MAIT cells leads to a reduction of HCV replication in vitro mediated by IFN-γ. Together these data demonstrate MAIT cells are activated following viral infections, and suggest a potential role in both host defence and immunopathology.